On the Triple Role of Fluoride Ions in Palladium‐Catalyzed Stille Reactions. Issue 50 (9th November 2015) - Hervé, Marius; Lefèvre, Guillaume; Mitchell, Emily A.; Maes, Bert U. W.; Jutand, Anny
Abstract: The mechanism of Stille reactions (cross‐coupling of ArX with Ar′Sn n Bu3 ) performed in the presence of fluoride ions is established. A triple role for fluoride ions is identified from kinetic data on the rate of the reactions of trans ‐[ArPdBr(PPh3 )2 ] (Ar=Ph, p ‐(CN)C6 H4 ) with Ar′SnBu3 (Ar′=2‐thiophenyl) in the presence of fluoride ions. Fluoride ions promote the rate‐determining transmetallation by formation of trans ‐[ArPdF(PPh3 )2 ], which reacts with Ar′SnBu3 (Ar′=Ph, 2‐thiophenyl) at room temperature, in contrast to trans ‐[ArPdBr(PPh3 )2 ], which is unreactive. However, the concentration ratio [F − ]/[Ar′SnBu3 ] must not be too high, because of the formation of unreactive anionic stannate [Ar′Sn(F)Bu3 ] − . This rationalises the two kinetically antagonistic roles exerted by the fluoride ions that are observed experimentally, and is found to be in agreement with the kinetic law. In addition, fluoride ions promote reductive elimination from trans ‐[ArPdAr′(PPh3 )2 ] generated in the transmetallation step. Abstract : Fluoride does the job : Three roles for fluoride ions in Stille reactions are identified from kinetic data. F − promotes the rate‐determining transmetallation by formation of trans ‐[ArPdF(PPh3 )2 ], which reacts with Ar′SnBu3, in contrast to trans ‐[ArPdBr(PPh3 )2 ], which does not. F − also promotes the reductive elimination in trans ‐[ArPdAr′(PPh3 )2 ]. However, the concentration ratio [F − ]/[Ar′SnBu3 ] must be less than 1 because of the formation of unreactive [Ar′Sn(F)Bu3 ] − .